2019
DOI: 10.1002/jper.19-0317
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Linc‐RNA activator of myogenesis lncRNA participates in FGF2‐mediated proliferation of human periodontal ligament stem cells

Abstract: Background Accelerated proliferation of human periodontal ligament stem cells (PDLSCs) is present in periodontitis. It is known that fibroblast growth factor 2 (FGF2) regulates the proliferation of PDLSCs, while the function of FGF2 in myogenic cell differentiation is mediated by Linc‐RNA Activator of Myogenesis (Linc‐RAM) lncRNA. Therefore, Linc‐RAM lncRNA may also participate in periodontitis. Methods This study included 28 patients with periodontitis (patient group) and 22 patients without periodontitis but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Table 3 presents 18 studies that investigated the role of lncRNAs in regulating cellular processes in PDL cells in the presence or absence of stimuli, including studies that compared H-PDL and P-PDL cells [ 60 , 61 , 62 , 63 , 64 , 65 ]. These studies also explored the role of lncRNAs in lipopolysaccharide (LPS)-induced inflammation [ 66 , 67 , 68 , 69 , 70 , 71 ], tumor necrosis factor-alpha (TNF-α)-induced inflammation [ 72 ], mechanical stress [ 73 , 74 , 75 ], hypoxia [ 76 ], and oxidative stress [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 presents 18 studies that investigated the role of lncRNAs in regulating cellular processes in PDL cells in the presence or absence of stimuli, including studies that compared H-PDL and P-PDL cells [ 60 , 61 , 62 , 63 , 64 , 65 ]. These studies also explored the role of lncRNAs in lipopolysaccharide (LPS)-induced inflammation [ 66 , 67 , 68 , 69 , 70 , 71 ], tumor necrosis factor-alpha (TNF-α)-induced inflammation [ 72 ], mechanical stress [ 73 , 74 , 75 ], hypoxia [ 76 ], and oxidative stress [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…A previous study has suggested the expression changes of more than 80 LncRNAs in P-PDLSCs compared to normal PDLSCs .72 Among them, the expression of LncRNA-TWIST1 is positively related to the osteogenic differentiation ability of P-PDLSCs ,75 and up-regulating LncRNA-PTCSC3 or down-regulating LncRNA-RAM both promote the proliferation of P-PDLSCs. 76,77 Another LncRNA, PDLSC osteogenesis impairmentrelated lncRNA (LncRNA-POIR), serves as a competitive endogenous molecule of miR-182 that can increase the expression of forkhead box O1, which then binds to β-catenin with TCF-4 to inhibit the canonic Wnt signaling pathway. Therefore, LncRNA-POIR down-regulation in P-PDLSCs impairs their osteogenic differentiation by indirectly activating the canonic Wnt signaling pathway .…”
Section: Retained Dysfunction Of Resident Pdlscs Under Epigenetic Reg...mentioning
confidence: 99%
“…Periodontitis is characterized by an imbalance between proliferation and apoptosis of periodontal ligament cells (PDLCs) 55 . Accumulating evidence has demonstrated that various lncRNAs exert vital roles in the proliferation and apoptosis of periodontitis PDLCs (pPDLCs) 17,56‐63 . Fibroblast growth factor‐2 (FGF2) is a pivotal promoter of PDLSCs proliferation 64 .…”
Section: The Role Of Lncrnas In the Pathophysiology Of Periodontitismentioning
confidence: 99%
“…MALAT1, a lncRNA overexpressed in periodontitis PDLSCs (pPDLSCs), was reported to promote periodontitis progression by upregulating the expression of fibroblast growth factor‐2 (FGF2) 56 . Conversely, the Linc‐RNA activator of myogenesis (Linc‐RAM), which was downregulated in pPDLSCs, attenuated the enhancing effect of FGF2 on the cell proliferation 60 . In addition, long non‐coding RNA domain containing 1‐antisense (lncRNA DCST1‐AS1), TUG1, and maternally expressed gene 3 (MEG3) were also downregulated in pPDLSCs 63,65,66 .…”
Section: The Role Of Lncrnas In the Pathophysiology Of Periodontitismentioning
confidence: 99%